Building Digital Literacy for Informal Sector Workers in Malaysia - Meylia Elizabeth Ranu; Pahlevi, Triesninda; Hermanto, Febrika Yogie; Nugraha, Jaka (Indonesian Journal of Society Development, 2024)
The purpose of this proposal refers to providing knowledge, understanding, and implementation of digital administrative literacy for migrant workers to be wise in using digital media for population administration activities. The presence of migrant workers abroad has its own challenges in storing population documents. One effort to realize this is by conducting training for migrant workers in Malaysia. The method of activity is community education by using training and approaches to targeted partners, implementing training and evaluation. From this activity, data was taken to see the achievement of objectives using questionnaire techniques. Data processing with descriptive analysis provides information that: 1) this training activity is very beneficial for Migrant Workers, 2) migrant workers have increased their digital administrative literacy competencies, 3) there is new knowledge and experience gained by training participants about the use of digital technology in population administration in daily activities, and 4) the attendance rate of activity participants reached 100%